2016
DOI: 10.1038/ncomms13147
|View full text |Cite
|
Sign up to set email alerts
|

The GCN5-CITED2-PKA signalling module controls hepatic glucose metabolism through a cAMP-induced substrate switch

Abstract: Hepatic gluconeogenesis during fasting results from gluconeogenic gene activation via the glucagon–cAMP–protein kinase A (PKA) pathway, a process whose dysregulation underlies fasting hyperglycemia in diabetes. Such transcriptional activation requires epigenetic changes at promoters by mechanisms that have remained unclear. Here we show that GCN5 functions both as a histone acetyltransferase (HAT) to activate fasting gluconeogenesis and as an acetyltransferase for the transcriptional co-activator PGC-1α to inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 36 publications
(69 reference statements)
0
34
0
Order By: Relevance
“…Gcn5 has been shown to be especially important for hepatic metabolism and may also be an anti-cancer target [12,56,57]. Like p300/CBP, Gcn5 also possesses a bromodomain (Figure 1), and the role of its bromodomain has been explored in the context of histone site selectivity.…”
Section: Catalytic Regulation Of Gcn5 By Its Bromodomainmentioning
confidence: 99%
“…Gcn5 has been shown to be especially important for hepatic metabolism and may also be an anti-cancer target [12,56,57]. Like p300/CBP, Gcn5 also possesses a bromodomain (Figure 1), and the role of its bromodomain has been explored in the context of histone site selectivity.…”
Section: Catalytic Regulation Of Gcn5 By Its Bromodomainmentioning
confidence: 99%
“…GCN5 acetylates and inactivates peroxisome proliferator-activated receptor c coactivator-1a (PGC-1a), thereby regulating the expression of many genes required by various cellular metabolic pathways, including fatty acid oxidation and gluconeogenesis [19,26]. Animal models showed that the expression of GCN5 is increased by a high-fat diet and decreased by fasting [22,30]. Animal models showed that the expression of GCN5 is increased by a high-fat diet and decreased by fasting [22,30].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being activated by its coenzyme acetyl-CoA, the acetyltransferase activity of GCN5 can also be up-regulated by the essential amino acid methionine and insulin-GSK3b signals [27][28][29]. Animal models showed that the expression of GCN5 is increased by a high-fat diet and decreased by fasting [22,30]. All these results indicate a role for GCN5 in cell energy homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Readers, writers and erasers in diabetes. Modification of the diabetic epigenome includes post-translational modifications to the tails of histones, carried out by histone-modifying enzymes (known a ‘writers’), such as SET7 [ 24 , 26 , 30 , 102 , 103 , 106 , 107 ], SETDB1 [ 108 ], SUV39H1 [ 109 , 110 ], EZH2 [ 40 , 111 ], KAT2A [ 42 , 112 ] and GLYATL1 [ 113 ]. Experimental studies that provide mechanistic insights for specific determinants are grouped to include the enzyme and corresponding modified histone, whereas informative profiling studies using clinical cohorts are separated with examples such as SET7 [ 30 ], SUV39H1/H2 [ 107 ], H3K9 acetylation [ 31 ] and H3K9me2 [ 82 ].…”
Section: Glycaemic Memories and Vascular Complications Of Diabetesmentioning
confidence: 99%